PENDAMPINGAN ORANG TUA SISWA TK DWP PDAM TIRTA MUSI PALEMBANG TENTANG MEMELIHARA KESEHATAN GIGI - Wahyuni, Sri; Hanum, Nur Adiba; Widodo, Yufen (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
One indicator of the quality of human life is health. Maintaining an optimal quality of life can be started from maintaining healthy teeth and mouth because if not treated it will cause pain, chewing problems and can interfere with order body health. The most common dental disease that affects the teeth is dental caries. The most appropriate prevention of caries should start with the growth of baby teeth. Because the quality of baby teeth will affect permanent teeth. The growth of milk teeth appears from the age of the child 3-8 months, and last until the age of 2-4 years. Based on interviews with teacher that at TK DWP PDAM Tirta Musi Palembang there had never been any counselin on dental health, both to their children and their parents and based on eamination at the kindergarten, many children suffered from dental caries, therefore provide dental health eduction to parents of students about maintaining dental health to improve quality.